Phytohormone complex of Cephalanthera damasonium (Mill.) Druce (gen. Orchidaceae Juss.) and its role in the development of reproduction methods in vitro - Sheyko, E.A.; Musatenko, L. I. (Reports of the National Academy of Sciences of Ukraine, 2014)
The article deals with studies of the components of the Cephalanthera damasonium (Mill.) Druce phytohormonal complex at the various stages of ontogenesis and with the elaboration of approaches to its introduction into the culture in vitro. It has been shown that, during ontogenesis, the contents of cytokinin, IAA, and ABA in the organs of C. damasonium, change, and the ratio of active and bound phytohormone forms varies. During the transition to the reproductive development, the contents of IAA and cytokinins in the orchid generative organs increase, and those of the vegetative organs decrease. The interrelation of callusogenesis intensity of C. damasonium vegetative and generative organs explants and the content and the ratio of the phytohormonal complex components at the specified stages of ontogenesis is first found. This must be taken into account in the elaboration of methods of microclonal reproduction of this species.